Adsorption of methanol on Si(100)/SiO(2)and mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Mathew, Nevin T.; Ravi, V.; Jacob, Nalini E.; Patil, K. R. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2006)
Adsorption of methanol on SiO(100)/SiO2 substrate and mesoporous SBA-15 has been studied by using Fourier transform infrared (FTIR) and X-ray photoelectron spectroscopy (XPS). Contact angle technique is employed to study the adsorption kinetics of methanol on SiO(100)/SiO2 and thermal stability of adlayer. Thermogravimetric (TGA) technique is used to understand the thermal behavior of methanol layer on SBA-15. Adsorption kinetics fit fairly well with Langmuir isotherms giving adsorption rate constant, k(a) = 0.0021 W s(-1). FTIR results show formation of methoxy silicon (SiOCHA silicon polyhydride (SiH2), carboxylate, molecular water and hydroxyl groups on Si(100)/SiO2 surface and only methoxy silicon on SBA-15. XPS results confirm methanol adsorption and support FTIR results. The methanol adlayers are found to be thermally stable up to a temperature of similar to 262 degrees C on both Si(100)/SiO2 and SBA-15 and decompose between 262 and 450 degrees C. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Adsorption; desorption; kinetics; Methanol; SBA-15; Si(100)/SiO2; thermal stability

Adsorption of octadecyltrichlorosilane on mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Sawant, Dhanashri P.; Jacob, Nalini E.; Patil, K. R.; Gaikwad, A. B.; Pradhan, S. D. (Applied Surface Science, 2006)
Adsorption of octadecyltrichlorosilane (OTS) on mesoporous SBA-15 has been studied by using Brunauer-Emmett-Teller (BET) surface area analysis, scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDAX), Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS) and thermo-gravimetric analysis (TGA) techniques. BET surface area analysis shows decrease of surface area from 930 to 416 m(2)/g after OTS adsorption. SEM pictures show close attachment of SBA-15 particles. EDAX measurements show increase of carbon weight percentage and decrease of oxygen and silicon weight percentage. XPS results closely support EDAX analysis. FTIR spectra shows presence of methyl (-CH3) and methylene (-CH2) bands and oriented OTS monolayer on SBA-15. Thermo-gravimetric analysis shows that the OTS adsorbed on SBA-15 are stable up to a temperature of 230 degrees C and that the OTS monolayers decompose between 230 and 400 degrees C. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Adsorption; OTS; SBA-15; Self-assembly; thermal stability

Adsorption of methanol on mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Mathew, Nevin T.; Jacob, Nalini E.; Patil, K. R.; Gaikwad, A. B. (Materials Letter, 2007)
The adsorption of methanol onmesoporous SBA-15 has been studiedbyrising Brunauer-Emmett-Teller (BET) surface area analysis, scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, X-ray photoclectrom spectroscopy (XPS) and tbennogravimettic analysis (TGA). The BET surface area analysis shows decreases of the surface area from 387 to 383 m(2)/g, pore volume from 0.88 to 0.81 cm(3)/g and pore diameter from 9.07 to 8.4 mm after methanol adsorption. The appearance of strong IR bands at 2862 and 2964cm(-1) due to methyl (-CH3) symmetric and asymmetric stretching demonstrate the presence of methanol and evidence of successful methanol adsorption. XPS results show increase of carbon and oxygen content on the surface of SBA-15. Thermogravirriettic analysis shows that the methanol adsorbed on SBA-15 is stable up to a temperature of 265 degrees C and that the methanol adlayers decompose between 265 and 588 degrees C. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Electron microscopy; Methanol; SBA-15; Surfaces; thermal stability

Au-Pt nanoparticles in amine functionalized MCM-41: catalytic evaluation in hydrogenation reactions - Joseph, Trissa; Kumar, K. Vijay; Ramaswamy, A. V.; Halligudi, Shivaraj B. (Catalysis Communications, 2007)
Nano-sized Au-Pt nanoparticles (Au-Pt-bi-MNPs) have been synthesized by the simultaneous reduction of HAuCl4 and HPtCl6 by NaBH4 inside the channels of amine functionalized Si-MCM-41 (NH2-Si-MCM-41) at ambient conditions. These materials were characterized using chemical analysis, UV-vis, XPS, XRD, FT-IR, Surface area and TEM analysis. The size of these alloyed nanoparticles (bi-MNPs) were found in the range of 2-4 nm. These nanoparticles were evaluated to study their catalytic activities towards hydrogenation of aromatic nitro compounds. The catalytic activity of the Au-Pt bi-MNPs was found to be superior to monometallic An nanoparticles. (c) 2006 Published by Elsevier B.V.
Keywords: amine-functionalized MCM-41; Au-Pt nanoparticles; Catalytic hydrogenation

Alkene epoxidation catalyzed by vanadomolybdophosphoric acids supported on hydrated titania - Ingle, Rohit H.; Vinu, A.; Halligudi, Shivaraj B. (Catalysis Communications, 2008)
Vanadomolybdophosphoric acids wet-impregnated oil hydrated titania (TiO(2) - xH(2)O), make ail efficient catalytic system for the epoxidation of a variety of alkenes with organic solvent extracted TBHP as the oxidant. By,in appropriate choice of solvent, the catalyst call be reused at least three times without much loss in the activity for subsequent runs. XRD shows that the heteropoly acid is uniformly dispersed over the support and up to 15 wt% loading of the heteropoly acid, no additional peak of the same call be seen in the XRD pattern of the catalyst. The reactivity varied with the nature of alkene but the major product was always the corresponding epoxide. The catalytic system is free of high temperature calcination steps and tedious multi-step procedures, normally encountered in the heter-ogenization of heteropoly acids. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: alkenes; epoxidation; heteropoly acids; TBHP; titania; vanadomolybdophosphoric acids